Three-Year Clinical Outcomes and Quality of Life after Retromuscular Resorbable Mesh Repair Using Fibrin Glue. Issue 6 (15th April 2022) - Morris, Martin P.; Patel, Viren; Christopher, Adrienne N.; Broach, Robyn; Harbison, Sean P.; Fischer, John P.
Abstract : Background: With 400, 000 hernias repaired annually, there is a need for development of efficient and effective repair techniques. Previously, the authors' group compared perioperative outcomes and hospital costs of patients undergoing ventral hernia repair with retromuscular mesh using suture fixation versus fibrin glue. This article reports on 3-year postoperative outcomes, including hernia recurrence, long-term clinical outcomes, and patient-reported quality of life. Methods: Patients who underwent ventral hernia repair performed by a single surgeon between 2015 to 2017 were identified. Patients with retromuscular resorbable mesh placed were included and matched by propensity score. Primary outcomes included hernia recurrence, surgical-site infection, surgical-site occurrence, and surgical-site occurrence/surgical-site infection requiring procedural interventions. Secondary outcomes included quality of life as assessed by the Hernia-Related Quality of Life Survey. Results: Sixty-three patients were eligible, and 46 patients were matched (23 suture fixation and 23 fibrin glue), with a median age of 62 years, a median body mass index of 29 kg/m 2, and a median defect size of 300 cm 2 (interquartile range, 180 to 378 cm 2 ). Median follow-up was 36 months (interquartile range, 31 to 36 months). There was no difference in the incidence of hernia recurrence (13.0 percent for suture fixation and 8.7 percent for fibrin glue; p = 0.636) or other postoperative outcomes between techniques (all p > 0.05). Five patients required reoperation because of a complication (10.9 percent). Overall quality of life improved preoperatively to postoperatively at all time points (all p < 0.05), and no differences in quality-of-life improvement were seen between techniques ( p > 0.05). Conclusion: Ventral hernia repair with atraumatic resorbable retromuscular mesh fixation using fibrin glue demonstrates equivalent postoperative clinical and quality-of-life outcomes when compared to mechanical suture fixation. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.